Comparison of technical efficiency between cooperative member and non-member farmers : a case of small-scale sugarcane farmers in the Nkomazi Local Municipality, Mpumalanga province, South Africa - Mkhabela, Lonhlanhla Samantha (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.